Plagiarism in Publications Using the Unpublished Raw Data of Archived Research - Yahaghi J.; Beddu S.B.; Muda Z.C. (Springer Netherlands, 2023)
ethics; information center; personnel; publication; publishing; research; research ethics; statistics and numerical data; Archives; Ethics, Research; Plagiarism; Publications; Research; Research Personnel